Academic writing and reader engagement contrasting questions in English, French, and Spanish corpora - Curry, Niall (Routledge applied corpus linguistics, 2021)
"Academic Writing and Reader Engagement offers a concise linguistic description of the use and functions of questions in English, French and Spanish and discusses their value to the teaching of academic writing. This book: Enables a better understanding of how writers engage readers in academic writing in English, French, and Spanish and where each language behaves similarly or differently; Explains how authors express opinions, organise discourse and create relationships with readers via questions in their academic writing and the various functions questions perform; Brings together research on corpus and contrastive linguistics, highlighting how these two fields can support one another; Offers a thorough investigation of reader engagement markers from a range of linguistic perspectives and considers how knowledge of these markers could be applied to the teaching and learning of academic writing in English, French and Spanish; Employs corpus data totalling approximately 400,000 words from all three languages to illustrate the varying roles and representations of questions in each language. Providing an invaluable resource for scholars learning to communicate successfully within their academic community, as well as teachers of English, French and/or Spanish for academic purposes, this book is key reading for students and researchers of academic discourse, contrastive linguistics and corpus linguistics"--Provided by publisher.